Deterministic radiative coupling between plasmonic nanoantennas and semiconducting nanowire quantum dots. (22nd March 2016) - Jeannin, Mathieu; Rueda-Fonseca, Pamela; Bellet-Amalric, Edith; Kheng, Kuntheak; Nogues, Gilles
Abstract: We report on the deterministic coupling between single semiconducting nanowire quantum dots emitting in visible and plasmonic Au nanoantennas. Both systems are separately and carefully characterized through micro-photoluminescence and cathodoluminescence. A two-step realignment process using cathodoluminescence allows for electron-beam lithography of Au antennas near individual nanowire quantum dots with a precision of 50 nm. A complete set of optical properties was measured before and after antenna fabrication. They evidence both an increase of the nanowire absorption, and an improvement of the quantum dot emission rate up to a factor of two in presence of the antenna.